Q&A - Ask Doubts and Get Answers
Q

Verify that a ÷ (b + c) ≠ (a ÷ b) + (a ÷ c) for each of the following values of a, b and c. (a) a = 12, b = – 4, c = 2 (b) a = (–10), b = 1, c = 1

2. Verify that a \div (b + c) \neq (a\div b)+ (a\div c) for each of the following values of a, b and c.
     (a) a = 12, b = – 4, c = 2            (b) a = (–10), b = 1, c = 1

Answers (1)
Views

a \div (b + c) \neq (a\div b)+ (a\div c)

(a) a = 12, b = – 4, c = 2   

L.H.S = \\ a \div (b + c)

\\ = 12 \div [(-4)+2] \\ = 12 \div (-2) \\ = - \left (\frac{12}{2} \right ) \\ = -6

R.H.S = (a\div b)+ (a\div c)

\\ = [12\div (-4)]+ (12\div 2) \\ = \left [-\left (\frac{12}{4} \right ) \right ] + \left (\frac{12}{2} \right ) \\ = (-3)+6 \\ = 3

Therefore. L.H.S \neq R.H.S

Hence verified.

 

(b) a = (–10), b = 1, c = 1

L.H.S = \\ a \div (b + c)

\\ = (-10) \div [1+1] \\ = (-10) \div 2 \\ = - \left (\frac{10}{2} \right ) \\ = -5

R.H.S = (a\div b)+ (a\div c)

\\ = [(-10)\div 1]+ ((-10)\div 1) \\ = \left [-\left (\frac{10}{1} \right ) \right ] + \left [-\left (\frac{10}{1} \right ) \right ] \\ = (-10)+(-10) \\ = -20

Therefore. L.H.S \neq R.H.S

Hence verified.

 

Exams
Articles
Questions